2016
DOI: 10.1159/000445618
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Improved Aldo-Induced Podocyte Injury via Inhibiting Oxidative Stress and Endoplasmic Reticulum Stress Pathways both In Vivo and In Vitro

Abstract: Background/Aims: Berberine, a naturally occurring isoquinoline alkaloid, acts against oxidative stress (OS) and endoplasmic reticulum stress (ERS), both of which are responsible for Aldosterone (Aldo) -induced podocyte injury. However, the direct effects of berberine on Aldo-induced OS, ERS, and podocyte injury are not well defined. Methods: Uninephrectomized Sprague-Dawley rats were given 1% NaCl (salt) in their water and an Aldo infusion (0.75 µg/h) for 28 days to induce podocyte injury in the Aldo group. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…Previous studies have demonstrated that beta-sitosterol has been widely used in the treatment of proteinuria resulting from diabetes and kidney disease [63][64][65]. Berberine has also been reported to treat proteinuria and kidney damage caused by diabetes and hypertension [66][67][68], which provided evidence for our results.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have demonstrated that beta-sitosterol has been widely used in the treatment of proteinuria resulting from diabetes and kidney disease [63][64][65]. Berberine has also been reported to treat proteinuria and kidney damage caused by diabetes and hypertension [66][67][68], which provided evidence for our results.…”
Section: Discussionsupporting
confidence: 79%
“…Over-activated or prolonged ER stress may initiate cellular apoptosis through two principal unfolded protein response (UPR) receptors inositol-requiring enzyme (IRE-1) and protein kinase RNA-like ER kinase (PERK) [16, 17]. It was reported that oxidative stress and ER stress pathways participate in Aldo-induced podocyte injury [18]. Notably, research shows that a cross talk exists between ER stress and the mammalian target of rapamycin (mTOR) signaling, another important signaling pathway that regulates cell survival [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Podocyte damage, such as alterations in the structure of podocytes or loss of podocytes will affect the integrity of the glomerular filtration barrier, resulting in proteinuria, thus promoting the progression of DN [7, 8]. Accumulating evidence indicates that DN is more like a “podocyte disease” [9-11]. Some clinical studies [12, 13] showed that the number of podocytes was reduced by detachment, or apoptosis as the primary reason.…”
Section: Introductionmentioning
confidence: 99%